PERBEDAAN A BODY SHAPE INDEX DAN BODY MASS INDEX SEBAGAI PREDIKTOR HIPERTENSI PADA PNS PRIA KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK KALIMANTAN BARAT DI PONTIANAK Tahun 2014 - ., Handy Eka Bayu (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Body Mass index (BMI) has long been used to evaluate thebody mass and is used to assess a person's health risks. A Body ShapeIndex (ABSI), a new measurement method showed better correlation to theaverage incidence of mortality compared with BMI. Body weight and bloodpressure are closely related, as weight gain, blood pressure will rise.Objective: to compare BMI and ABSI as a predictor of hypertension in menworkers tax office West Kalimantan Pontianak. Method: This study usedcross-sectional design, 43 subjects, aged 24-60 years, men were taken. allwere measured blood pressure, waist circumference, weight and height,then ABSI and BMI value were calculated. Result: BMI mean is 26,43. ABSImean is 0,07. Systolic blood pressure mean is 121,39 mmHg. Diastolicblood pressure mean is 81,60 mmHg. There was no significant correlationbetween BMI or ABSI compared to blood pressure(p=0, 240 and p=0,692).Conclusion: ABSI nor BMI had no significant relationship to bloodpressure.Key Words: Body Mass Index, A Body Shape Index, Blood PressureNote:1. Medical School, Faculty of Medicine, University Of Tanjungpura,Pontianak, West Kalimantan.2. Departement Of Nutrition, Faculty of Medicine, University OfTanjungpura, Pontianak, West Kalimantan.3. Departement Of Physiology, Faculty of Medicine, University OfTanjungpura, Pontianak, West Kalimantan.